The University As Constructed Cultural Commons - Michael J. Madison; Brett M. Frischmann; Katherine J. Strandburg (Washington University Journal of Law & Policy, 2009)
This Article illustrates an agenda for investigating the mechanics of innovation contexts.
Keywords: Intellectual property; Public domain (Copyright law); Technological innovations; Universities and colleges